Risk and the law [electronic resource] - Klippel, Diethelm; Woodman, Gordon R. (London ; New York : Routledge-Cavendish, 2009)
This volume brings together international experts to examine the implications in practice of the modern concept of risk in particular legal fields. The papers question how the law can accommodate, manage, and reduce the extent of risk, a matter of press
Description based on print version record
Includes bibliographical references and index
Keywords: Juristic acts; Liability (Law); Risk; Risk assessment